2013
DOI: 10.1016/j.matdes.2013.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Low cycle fatigue life improvement of AISI 304 by initial and intermittent wire brush hammering

Abstract: The effects of hammering by wire brush as a method of improving low cycle fatigue life of highly ductile austenitic stainless steel AISI 304 have been investigated through an experimental study combining imposed strain fatigue tests and assessment of surface characteristic changes under cyclic loading by SEM examinations and XRD analysis. It has been shown that the fatigue life of wire brush hammered surface was increased by 307% at an imposed strain rate of 0.2% and only 17% at an imposed strain rate of 0.5%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 24 publications
8
22
0
Order By: Relevance
“…In this case, the effective stress intensity is reduced by the negative residual stress intensity factor. These observations are in good agreement with both experimental and modelling results reported in the literature for both ductile and hard materials . Indeed, the turning process produces tensile or very low compressive residual stresses in both loading and transverse directions ( σ 0 = −14 MPa in the loading direction and σ 90 = +340 MPa in the transverse direction), whereas subsequent wire brush hammering operation reverses those residual stresses to induce highly compressive ones ( σ 0 = −846 MPa and σ 90 = −750 MPa in the same directions, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this case, the effective stress intensity is reduced by the negative residual stress intensity factor. These observations are in good agreement with both experimental and modelling results reported in the literature for both ductile and hard materials . Indeed, the turning process produces tensile or very low compressive residual stresses in both loading and transverse directions ( σ 0 = −14 MPa in the loading direction and σ 90 = +340 MPa in the transverse direction), whereas subsequent wire brush hammering operation reverses those residual stresses to induce highly compressive ones ( σ 0 = −846 MPa and σ 90 = −750 MPa in the same directions, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…This high surface hardness is expected to contribute significantly to the enhancement of fatigue crack initiation resistance near surface as reported in previous studies. 10,12 Ben Fredj et al 10 reported a 26% increase in the high cycle fatigue strength of a ground and brushed AISI 304 stainless steel sample, whereas Makhlouf et al 12 reported an increase in low cycle fatigue life by 307% at a strain amplitude Δε t /2 = 0.2% for a turned AISI 304 stainless steel. This last value is of the same order of magnitude (266%) found in this study for AISI 316.…”
Section: Contribution Of Surface Cold Work Hardeningmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows a fatigue lifetime decreasing with an increase in the rebuilt material density. This result is in accordance to the well‐known detrimental effect of tensile residual stress on the fatigue crack nucleation, which considered as damaging stress …”
Section: Discussionsupporting
confidence: 90%
“…Higher is the rebuilt material density, rapid is the fatigue crack coalescence and lower fatigue life is. This phenomenon is strongly associated with the high tensile residual stress field as supported by Makhlouf et al . observations for the AISI 304.…”
Section: Discussionsupporting
confidence: 62%